Analysis of Financial Management Performance of TPQ Ma'ba'ul Khoir Jombang in the SAK 45 Reporting Framework - Putra, Saiful Aminudin Al Kusuma; Hikmah, Nuril; Amri, Fahimul (Journal of Economics and Social Sciences (JESS), 2025)
The financial reports of non-profit entities, such as the Al-Qur'an Education Park (TPQ), serve as an instrument of accountability and transparency in resource management. This study aims to analyze the implementation of Financial Accounting Standards (SAK) No. 45 concerning Financial Reporting of Non-Profit Entities at TPQ Mamba'ul Khoir, Jombang Regency. This qualitative research uses primary data sources from interviews with administrators and secondary data in the form of TPQ financial reports. The analysis was conducted by comparing TPQ's recognition, measurement, and reporting practices with the principles of SAK 45. The findings indicate that TPQ Mamba'ul Khoir has not implemented SAK 45. Its accounting practices still rely on a simple cash basis, where recording focuses only on cash inflows and outflows. This limitation is evident in the absence of a net asset classification (restricted/unrestricted) and the lack of a comprehensive statement of financial position, which hinders transparency. This study reconstructs the TPQ's financial reports into SAK 45 format as a recommendation. However, the final results found that the accounts in the TPQ's simplified financial statements were more similar when adjusted to SAK 109 (Accounting for Zakat, Infaq, and Sedekah) than to SAK 45, given the nature of religious organizations. The main inhibiting factors in implementation were limited understanding among management and competent human resources. In conclusion, TPQ Mamba'ul Khoir needs to shift from a cash basis to an accrual basis and adopt more relevant accounting standards (SAK 109 is recommended)